The Rock Island Line is Mighty Fine Line - Andy Piasecki (Communications - Scientific letters of the University of Zilina, 2000)
Research into information and communication technologies tends to be dominated by the perspectives of technological determinism and theories of social shaping. Actor-network theory has emerged as an alternative approach for understanding and interpreting sociotechnical change. It has been applied to a wide variety of technologies and been used to explore how technology both constructs and is constructed by different stakeholder groups and how companies promote their interests through published texts and the courts to “seize control“ of technological developments (Bowker, 1992). This article borrows from actor-network theory in order to explore how influential actors in the process of social change attempt to stabilise forces to their own advantage. By way of analogy with the rapid development of a global communication infrastructure for cable, telephone, PC, TV services etc., the article focuses on the most significant development in the communication infrastructure during the nineteenth century - railways, and in particular on the role of this technology in the opening up of the American West.